Análise da qualidade de vida no trabalho utilizando um modelo de regressão logística - Batista, Álamo Alexandre da Silva (2010)
The objective of this study was to identify witch sociodemographic variables and shift working have significant influence on quality of working life of employees on the dairy industry. The methodological approach was applied, descriptive and qualitativequantitative, held through a documents review. For the analyze and interpretation of the data it was used the model adapted from Walton, by a Likert scale, to rate the quality of working life of the studied population, being formed for 548 employees. For data analysis it was used the chi-square and logistic regression analysis. For validating the model estimated by logistic regression analysis, it was used the Deviance, Pearson and Hosmer-Lemeshow tests. The results showed that the variables education, number of children, smoking, physical activity, working time and alcohol consumption did not have significant influence over the QVT of this population, because it presented values above the significant level adopted (P>0,05). The variables gender (P=0,015), age (P=0,045), marital status (P=0,017) and shift working (P=0,012) had a significant influence on QVT. Considering these variables it was estimated a mathematical model using the logistic regression analysis, and the odds ratio (OR) was found: the gender factor (OR = 1.84) for age (OR = 0.95), for marital status (OR = 0.64), for shift 2 (OR = 3.16) and shift 4 (OR = 2.50). It was concluded that the managers of this segment in intention to establish/ improve QWL programs for the studied population, can direct their investments in employees male, young, single and working on shifts 2 or 4.